Épistémologies de la pédagogie, relations aux savoirs et à la didactique - Bruno Robbes (Éducation et Socialisation)
I propose to further explore the epistemological status of pedagogy by investigating six lines of reflection. This analysis shows that while pedagogical knowledge takes on specific features compared to scientific knowledge, some similarities suggest links between these two types of knowledge. Such links allow the identification of three distinct conceptions of the relationship between research and pedagogy. I also study some current and convergent perspectives offering an opportunity to overcome the opposition between knowledge, didactics and pedagogy. These views open up new research perspectives on teaching and on learning/knowledge-acquisition processes, considered as multidimensional phenomena, though they raise questions about the conditions of possibility of such processes and the type of research implemented.